IMPACT OF MULTIPROBIOTICS ON THE CONTENT OF TBA-REACTIVE SUBSTANCES IN THE BLOOD SERUM AND MUCOUS MEMBRANES OF THE STOMACH AND COLON IN RATS WITH LONG-TERM GASTRIC HYPOCHLORHYDRIA - Pylypenko, S.V.; Koval, A.A.; Makarchuk, V.V. (World of Medicine and Biology, 2018)
It has been established that after 28 days of administering omeprazole to rats, the TBARS content had grown in all the studied media: in the blood serum, by 92.1% (p